Effect of plasma pretreatment on durability of sol-gel superhydrophobic coatings on laser modified stainless steel substrates. Issue 21 (2nd November 2018) - Pradheebha, S.; Unnikannan, R.; Bathe, Ravi N.; Padmanabham, G.; Subasri, R.
Abstract: Superhydrophobic surfaces were generated on stainless steel SS 304 substrates, using a combination of physical as well as chemical modification of the surface and tested for use in biomedical applications. Nanosecond pulsed laser was used for physical modification, i.e. creating nanoscaled roughness on the substrates. An additional chemical modification was performed using fluorosilane-based sol-gel nanocomposite coatings to further improve the hydrophobicity. Presently, the key challenge that such surfaces face, is to possess a substantial durability. In this study, a surface activation technique such as plasma pre-treatment was adopted to improve the adhesion of coatings on the laser treated substrates. The coatings deposited using dip coating technique were cured at 150 °C. The surface morphology and the roughness of the processed substrates and the coated samples were characterized using Atomic Force Microscope and Scanning Electron Microscope. The wettability of the surface was monitored and evaluated throughout the study using water contact angle measurements. Weathering tests and scratch resistance measurements using a crockmeter were carried out to evaluate the durability, which revealed that the adhesion could be improved with plasma treatment of the laser textured substrates, prior to coating deposition. Maximum anti-bacterial activity of up to 90% towards the bacterial species Escherichia coli was found on the substrates coated with the fluorosilane-based superhydrophobic coatings for an exposure time of 30 min, without any addition of external anti-bacterial agents. Thus, the preliminary results obtained from the present investigation were found to be promising and were indicative of use of these surfaces for biomedical applications.